PENGARUH ISLAMIC MARKETING TERHADAP KEPUASAN DAN LOYALITAS NASABAH PADA BANK MUAMALAT CABANG MALANG - Langgeng Setyono (Universitas Halu Oleo, 2021)
Indonesia is a country with a majority Muslim population. In the context of Indonesian’s, Muslims constitute a very large market share for marketing products, especially Islamic products. One of the products based on Islamic values is Islamic Bank. In Indonesia, Bank Muamalat is the first bank in existence. With such a large Muslim population, on the other hand, Islamic banks do not hold market share in the national banking industry. Islamic banks lag behind other conventional banks. Therefore, a strategy is needed to increase that market share. Islamic marketing is a strategy that can be used to increase customer satisfaction and loyalty at Bank Muamalat Indonesia.This research is an explanatory research with a quantitative approach. The sampling technique used in this study was purposive sampling. Respondents in this study were 120 people. The Machin and Campbell formula is used to determine the number of respondents. The objectives of this study are (1) to determine the effect of Islamic marketing on customer satisfaction; (2) to determine the effect of Islamic marketing on customer loyalty; (3) To determine the effect of customer satisfaction on customer loyalty.The results of this study are (1) Islamic marketing has a significant effect on customer satisfaction; (2) Islamic marketing has a significant effect on customer loyalty; and (3) Customer satisfaction has a significant effect on customer loyalty. So that Bank Muamalat in increasing customer satisfaction and loyalty needs to improve the existing indicators in Islamic Marketing